Immunoaffinity Purification of Protein Complexes from Mammalian Cells - Tomomori-Sato, Chieri (2013)
In this chapter, we describe a purification scheme designed to isolate multisubunit protein complexes gently and quickly from crude extracts of mammalian cells using immunoaffinity purification of epitope tagged proteins and the multisubunit complexes with which they associate. As an example we describe isolation of the mammalian Mediator complex from HeLa S3 cells.